Les textes littéraires dans le discours des manuels de français exploités en Pologne entre la fin du XXe siècle et les années vingt du XXIe siècle - Chmiel-Bożek, Halina (2023)
The article presents the results of a quantitative and qualitative analysis of textbooks for learning French for secondary schools in terms of the use of fragments of literary texts and the didactic goals assigned to them. The conducted study of 43 titles approved for educational use over the last twenty years in Poland reveals that in the majority of textbooks adapted to the 1999 core curriculum, fragments of literary texts appear and are used, in accordance with the communicative approach, mainly to develop key language competencies. Over time, a clear downward trend is noticeable, which means that in the current textbooks, adapted to the 2018 core curriculum, literary texts are practically non-existent, despite the possibilities offered by the action-oriented approach in this matter.
Keywords: literature; literary text; French textbooks; communicative approach; action-oriented approach; discourse of textbooks